Spontaneous and Excellent Healing of Bilateral Brown Tumors in Mandible after Endocrinal Therapy and Subtotal Parathyroidectomy: Case Report with 4-Year Follow-Up - Turker Yucesoy; Erdem Kilic; Fatma Dogruel; Fahri Bayram; Alper Alkan; Alper Celal Akcan; Figen Ozturk (Case Reports in Dentistry)
Primary hyperparathyroidism is an endocrine disorder occurring due to increased secretion of parathormone resulting in a complex of clinical, anatomical, and biochemical alterations. On the other hand, excision of a parathyroid adenoma can normalize the metabolic status. A 24-year-old man was referred to the hospital with bilateral swelling and spontaneous gingival bleeding from posterior of the mandible also with radiolucent well-demarcated lesions bilaterally in the mandibular third molar regions. After consultations, the patient was hospitalized in the endocrinology department where further tests were performed due to highly increased PTH level as 714 pg/ml. Bilateral brown tumors started to regress spontaneously, and no additional surgery was required after subtotal parathyroidectomy was performed. The presented case is the first patient whose bilateral brown tumors in the jaws spontaneously and totally healed after subtotal parathyroidectomy and endocrinal therapy who was strictly followed up for 4 years even though the lesions were associated with impacted third molars.